Preparation method of MOF-based mixed matrix membrane for treating tailing wastewater
By adding EDTA to UiO-66 and blending it with PVDF, a MOF-based mixed matrix membrane was prepared, which solved the problem of insufficient adsorption capacity of the existing UiO-66 base membrane on heavy metal ions, and achieved efficient interception and removal of various heavy metals in tailings wastewater.
Patent Information
- Application Number
- CN202510320028.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-18
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-18
AI Technical Summary
The existing UiO-66-based mixed matrix membrane only has a retention effect on Sb(V) ions in tailings wastewater and cannot effectively adsorb other heavy metal ions, such as Cr(VI) and Pb(II).
UiO-66-EDTA composite material was prepared by adding EDTA to UiO-66 and blended with polyvinylidene fluoride (PVDF) to prepare a MOF-based hybrid matrix membrane. This method forms a film with a high specific surface area and a porous structure through ultrasonic treatment and scraping techniques of cast film liquid.
It realizes efficient interception of heavy metal ions such as Sb(V), Cr(VI) and Pb(II) in tailings wastewater, improves the adsorption capacity and removal efficiency of the membrane, and maintains a high water flux.
Smart Images

Figure CN119869246A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a mixed matrix membrane for treating tailings wastewater. Background Art
[0002] Tailings wastewater is a complex pollutant produced during mining and mineral processing that contains high concentrations of heavy metal ions (such as lead, cadmium, arsenic, mercury, etc.) and acidic substances. It is highly toxic, difficult to degrade, and easy to enrich. According to statistics from the United Nations Environment Programme, more than 10 billion tons of tailings waste are produced each year worldwide, of which about 30% infiltrates into soil and water bodies due to improper treatment, causing ecosystem damage and public health risks. For example, the pH value of acid mine drainage (AMD) can be as low as 2-3, and is accompanied by Fe 3+ , Cu 2 + The migration of plasma seriously threatens the safety of the food chain. Although traditional treatment methods such as chemical precipitation, ion exchange and activated carbon adsorption are widely used, they have problems such as low efficiency, high cost and secondary pollution. For example, chemical precipitation easily produces a large amount of sludge, activated carbon is difficult to regenerate, and has limited adsorption capacity for low-concentration heavy metals. Therefore, it is urgent to develop a new treatment technology that is efficient, environmentally friendly and recyclable.
[0003] Metal-Organic Frameworks (MOFs) are porous crystalline materials formed by the self-assembly of metal ions / clusters and organic ligands. 2 / g), adjustable pore structure and surface functional groups, make it show great potential in the field of adsorption and catalysis. However, it is limited in practical application because it is easy to break into small particles or powder. In industrial processes such as catalysis and separation, these small particles or dust produced by fragmentation are easy to block pipes and even cause explosions, which seriously hinders the widespread application of MOFs materials. Therefore, it is particularly important to explore new MOFs processing and molding methods. At present, the common method in industry is to granulate MOFs powder, usually by high-pressure molding or adding adhesives to shape. However, the high-pressure granulation method may affect the properties of MOFs and reduce the efficiency of the device after molding; while the addition of adhesives will reduce the proportion of active ingredients of MOFs and weaken its performance. In addition, the reported MOFs membranes have problems such as poor stability and brittleness, and the production process consumes a lot of energy. However, blending MOFs with polymer materials (such as polyvinylidene fluoride) to make mixed matrix membranes can combine the excellent properties of both and show potential application prospects in tailings wastewater. Summary of the invention
[0004] The present invention aims to solve the technical problem that the existing UiO-66-based mixed matrix membrane only has an interception effect on Sb(V) ions in tailings wastewater, and provides a preparation method of a MOF-based mixed matrix membrane for treating tailings wastewater.
[0005] The preparation method of the MOF-based mixed matrix membrane for treating tailings wastewater of the present invention is carried out according to the following steps:
[0006] 1. adding the UiO-66-EDTA composite material into a solvent for dissolution, and performing ultrasonic treatment to obtain a suspension;
[0007] 2. Fully dissolving the suspension prepared in step 1 and polyvinylidene fluoride (PVDF) powder to form a casting solution, and then performing ultrasonic defoaming for 90 minutes;
[0008] 3. Scrape the casting liquid obtained in step 2 onto a glass plate to form a liquid film;
[0009] Fourth, place the glass plate with the liquid film in the air for pre-evaporation for 30s to 35s, then immerse it in deionized water at 27℃ to 29℃, and let it stand until the film and the glass plate are completely separated. Use tweezers to transfer the liquid film to another deionized water at room temperature and soak it for 24h to 25h to obtain a MOF-based mixed matrix membrane;
[0010] The mass of the MOF-based mixed matrix membrane is composed of the UiO-66-EDTA composite material of step one, the solvent and the polyvinylidene fluoride powder of step two, wherein the added amount of the UiO-66-EDTA composite material is 1wt% to 6wt%, and the added amount of the polyvinylidene fluoride powder is 6wt% to 11wt%.
[0011] Beneficial effects of the present invention:
[0012] Compared with UiO-66 alone, the present invention adds EDTA to UiO-66. Due to its strong complexation, EDTA will compete for the combination of organic ligands and zirconium clusters, thereby controlling and slowing down the growth rate of the crystal and filling some missing sites, obtaining UiO-66 nanoparticles with higher specific surface area and more uniform distribution, exposing more adsorption sites. This characteristic can not only adsorb more Sb(V) ions, but also increase the adsorption objects Cr(VI) and Pb(II) ions, that is, it can achieve the adsorption of multiple metal ions. The present invention utilizes the characteristics of MOF, such as ultra-high specific surface area, customizable structure, high-efficiency adsorption capacity and good compatibility with polymer matrix, to become a revolutionary material for tailings wastewater treatment. The monodispersed UiO-66-EDTA material is introduced into the PVDF membrane matrix by a blending modification method, and the shape and size of the membrane pores can be effectively adjusted to prepare a MOF-based mixed matrix membrane with multiple adsorption objects and high removal efficiency. The MOF-based mixed matrix membrane has a high retention rate for heavy metals such as Sb(V), Cr(VI) and Pb(II) in tailings wastewater, and has good anti-pollution performance, and can be applied to the treatment of tailings wastewater. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 The present invention is a flow chart of the preparation process of the MOF-based mixed matrix membrane for treating tailings wastewater;
[0014] Figure 2 This is the water flux test in experiment 1 and the separation performance data of Sb(V) ions in tailings wastewater. DETAILED DESCRIPTION
[0015] Specific embodiment 1: This embodiment is a method for preparing a MOF-based mixed matrix membrane for treating tailings wastewater, which is specifically carried out according to the following steps:
[0016] 1. adding the UiO-66-EDTA composite material into a solvent for dissolution, and performing ultrasonic treatment to obtain a suspension;
[0017] 2. Fully dissolving the suspension prepared in step 1 and polyvinylidene fluoride powder to form a casting solution, and then performing ultrasonic defoaming for 90 minutes;
[0018] 3. Scrape the casting liquid obtained in step 2 onto a glass plate to form a liquid film;
[0019] Fourth, place the glass plate with the liquid film in the air for pre-evaporation for 30s to 35s, then immerse it in deionized water at 27℃ to 29℃, and let it stand until the film and the glass plate are completely separated. Use tweezers to transfer the liquid film to another deionized water at room temperature and soak it for 24h to 25h to obtain a MOF-based mixed matrix membrane;
[0020] The mass of the MOF-based mixed matrix membrane is composed of the UiO-66-EDTA composite material of step one, the solvent and the polyvinylidene fluoride powder of step two, wherein the added amount of the UiO-66-EDTA composite material is 1wt% to 6wt%, and the added amount of the polyvinylidene fluoride powder is 6wt% to 11wt%.
[0021] Specific implementation method 2: This implementation method is different from the specific implementation method 1 in that the solvent in step 1 is N,N-dimethylacetamide. The rest is the same as the specific implementation method 1.
[0022] Specific embodiment 3: This embodiment is different from specific embodiment 1 or 2 in that: the preparation method of the UiO-66-EDTA composite material described in step 1 is:
[0023] (1) 240 mg of zirconium chloride was dissolved in 50 mL of acetone, and then 161 mg of terephthalic acid was added and ultrasonically mixed for 15 min to obtain a uniform precursor solution;
[0024] (2) transferring the precursor solution into a polytetrafluoroethylene-lined autoclave and placing it in a 120° C. oven for constant temperature crystallization for 48 h, taking out the autoclave and naturally cooling it to room temperature;
[0025] (3) After the obtained product was repeatedly washed with N,N-dimethylformamide and anhydrous ethanol, it was placed in a forced air drying oven and dried at 60°C for 12 h to obtain UiO-66 powder;
[0026] (4) 1.582 g of EDTA-2Na was dissolved in 50 mL of water and stirred to form a clear and transparent solution, followed by adding 0.1 g of UiO-66 powder and stirring at 60° C. for 24 h; the mixture was filtered and washed with deionized water, the solid portion was retained, and finally dried at 100° C. to obtain a UiO-66-EDTA composite material. The rest is the same as in the first or second embodiment.
[0027] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that: in step 2, magnetic stirring is performed for 24 hours to fully dissolve the polyvinylidene fluoride powder in the suspension. Other aspects are the same as those of specific embodiments 1 to 3.
[0028] Specific implementation mode 5: This implementation mode is different from specific implementation mode 4 in that the rotation speed of the magnetic stirring in step 2 is 300 rpm. The rest is the same as specific implementation mode 4.
[0029] Specific implementation example 6: This implementation example is different from specific implementation example 5 in that the specific process of step 3 is: using a glass plate as a substrate, setting the gap between the scraper and the glass plate to 200 μm, pouring the casting liquid on one side of the scraper, and quickly scraping a uniform liquid film on the glass plate by manual operation, the experimental conditions are room temperature and humidity of 40% to 50%. The rest is the same as specific implementation example 5.
[0030] The present invention is verified by the following tests:
[0031] Experiment 1: This experiment is a method for preparing a MOF-based mixed matrix membrane for treating tailings wastewater, which is specifically carried out in the following steps:
[0032] 1. 0.5 g of UiO-66-EDTA composite material was added to 8.8 g of solvent N, N-dimethylacetamide for dissolution, and ultrasonic treatment was performed for 10 min to obtain a suspension;
[0033] The preparation method of the UiO-66-EDTA composite material is as follows:
[0034] (1) 240 mg of zirconium chloride was dissolved in 50 mL of acetone, and then 161 mg of terephthalic acid was added and ultrasonically mixed for 15 min to obtain a uniform precursor solution;
[0035] (2) transferring the precursor solution into a polytetrafluoroethylene-lined autoclave and placing it in a 120° C. oven for constant temperature crystallization for 48 h, taking out the autoclave and naturally cooling it to room temperature;
[0036] (3) After the obtained product was repeatedly washed with N,N-dimethylformamide and anhydrous ethanol, it was placed in a forced air drying oven and dried at 60°C for 12 h to obtain UiO-66 powder;
[0037] (4) 1.582 g of EDTA-2Na was dissolved in 50 mL of water and stirred to form a clear and transparent solution, followed by adding 0.1 g of UiO-66 powder and stirring at 60 °C for 24 h; the mixture was filtered and washed with deionized water, the solid portion was retained, and finally dried at 100 °C to obtain a UiO-66-EDTA composite material;
[0038] 2. The suspension prepared in step 1 was fully dissolved with 0.7 g of polyvinylidene fluoride powder, and magnetically stirred for 24 h at a speed of 300 rpm to form a casting solution, and then ultrasonically defoamed for 90 min;
[0039] 3. The casting liquid obtained in step 2 is scraped onto a glass plate to form a liquid film. The specific process is as follows: with the glass plate as the substrate, the gap between the scraper and the glass plate is set to 200 μm, the casting liquid is poured onto one side of the scraper, and a uniform liquid film is quickly scraped onto the glass plate by manual operation. The experimental conditions are room temperature and humidity is 45%;
[0040] Fourth, place the glass plate with the liquid film in the air for pre-evaporation for 30 seconds, then immerse it in deionized water at 28°C. After standing for 5 minutes, the film is completely separated from the glass plate. Use tweezers to transfer the liquid film to another deionized water at room temperature and soak it for 24 hours to obtain a PVDF / UiO-66-EDTA mixed matrix membrane.
[0041] The mass of the PVDF / UiO-66-EDTA mixed matrix membrane is composed of the UiO-66-EDTA composite material in step one, the solvent and the polyvinylidene fluoride powder in step two, which is 10g.
[0042] Experiment 2: The difference between this experiment and experiment 1 is that the addition amount of UiO-66-EDTA composite material in step 1 is 0.6 g, and the addition amount of polyvinylidene fluoride powder in step 2 is adjusted to 0.6 g. The other conditions are the same as experiment 1.
[0043] Experiment 3: The difference between this experiment and experiment 1 is that the addition amount of UiO-66-EDTA composite material in step 1 is 0.4 g, and the addition amount of polyvinylidene fluoride powder in step 2 is adjusted to 0.8 g. The other conditions are the same as experiment 1.
[0044] Experiment 4: The difference between this experiment and experiment 1 is that the addition amount of UiO-66-EDTA composite material in step 1 is 0.3g, and the addition amount of polyvinylidene fluoride powder in step 2 is adjusted to 0.9g. The other conditions are the same as experiment 1.
[0045] Experiment 5: The difference between this experiment and experiment 1 is that the addition amount of UiO-66-EDTA composite material in step 1 is 0.2g, and the addition amount of polyvinylidene fluoride powder in step 2 is adjusted to 1g. The other conditions are the same as experiment 1.
[0046] Experiment 6: The difference between this experiment and experiment 1 is that the addition amount of UiO-66-EDTA composite material in step 1 is 0.1 g, and the addition amount of polyvinylidene fluoride powder in step 2 is adjusted to 1.1 g. The other conditions are the same as experiment 1.
[0047] Experiment 7: The difference between this experiment and experiment 1 is that UiO-66 is used to replace UiO-66-EDTA in step 1, and finally a PVDF / UiO-66 mixed matrix membrane is obtained. The other conditions are the same as those in experiment 1.
[0048] Experiment 8: The difference between this experiment and experiment 2 is that UiO-66-EDTA was replaced with UiO-66 in step 1, and a PVDF / UiO-66 mixed matrix membrane was finally obtained. The other conditions were the same as those in experiment 2.
[0049] Experiment 9: The difference between this experiment and experiment 3 is that UiO-66 is used to replace UiO-66-EDTA in step 1, and finally a PVDF / UiO-66 mixed matrix membrane is obtained. The other conditions are the same as those in experiment 3.
[0050] Experiment 10: The difference between this experiment and experiment 4 is that UiO-66 is used to replace UiO-66-EDTA in step 1, and finally a PVDF / UiO-66 mixed matrix membrane is obtained. The other conditions are the same as those in experiment 4.
[0051] Experiment 11: The difference between this experiment and experiment 5 is that in step 1, UiO-66 is used to replace UiO-66-EDTA, and finally a PVDF / UiO-66 mixed matrix membrane is obtained. The other conditions are the same as those in experiment 5.
[0052] Experiment 12: The difference between this experiment and experiment 6 is that in step 1, UiO-66 is used to replace UiO-66-EDTA, and finally a PVDF / UiO-66 mixed matrix membrane is obtained. The other conditions are the same as those of experiment 6.
[0053] The preparation method of UiO-66 is:
[0054] (1) 240 mg of zirconium chloride was dissolved in 50 mL of acetone, and then 161 mg of terephthalic acid was added and ultrasonically mixed for 15 min to obtain a uniform precursor solution;
[0055] (2) transferring the precursor solution into a polytetrafluoroethylene-lined autoclave and placing it in a 120° C. oven for constant temperature crystallization for 48 h, taking out the autoclave and naturally cooling it to room temperature;
[0056] (3) The obtained product was repeatedly washed with N,N-dimethylformamide and anhydrous ethanol, and then placed in a forced air drying oven and dried at 60° C. for 12 h to obtain UiO-66 powder.
[0057] Comparative test: The difference between this test and test 1 is that the addition amount of UiO-66-EDTA composite material in step 1 is 0, and the addition amount of polyvinylidene fluoride powder in step 2 is adjusted to 1.2g, and finally a PVDF membrane is obtained. The other conditions are the same as test 1.
[0058] Ultrafiltration experiments were conducted on the membranes prepared in the above experiments 1 to 12 and the comparative experiment, and flux tests were conducted using pure water. The specific method was as follows: the membrane was fixed in an ultrafiltration cup, 50 mL of deionized water was added to the ultrafiltration cup, and the air compressor and the ultrafiltration cup were connected after sealing. The membrane was pre-pressed for the first time at a pressure of 2 bar. After the membrane was pre-pressed, a stopwatch and a measuring cylinder were used to measure the volume of liquid passing through the membrane per unit time, and the water flux was calculated according to the following formula:
[0059]
[0060] In formula 1: J is the flux L / (m 2 ·h·bar), T is the test time (h), V is the volume of aqueous solution that passes through the membrane within time T (L), A is the effective membrane area (m 2 ).
[0061] Tailings wastewater from Fujian Zijin Mining, which contained 8 mg / L Sb(V), 10 mg / L Cr(VI), 12 mg / L Pb(II), and a pH of 5.6, was used for interception test. The interception rate is an important parameter for evaluating the separation performance of the membrane.
[0062]
[0063] In formula 2: R is the interception rate (%), C p is the concentration of ions in the raw material solution (mg / L), C f is the concentration of ions in the permeate (mg / L).
[0064] The difference between the test of interception rate and the test of pure water flux is that you only need to add 20mL of tailings wastewater after completing the test of pure water flux, and collect the filtrate to measure the concentration after all of it passes through the membrane.
[0065] According to the above formulas 1 and 2, the pure water flux of each membrane at a pressure of 1 bar and the retention rate of tailings wastewater (containing Sb(V), Cr(VI), and Pb(II) ions) can be calculated. The specific results are shown in Tables 1 and 2.
[0066] Table 1 Membrane retention rate for Sb(V) ions and pure water flux
[0067]
[0068] From the data in Table 1, it can be found that the maximum interception rate of PVDF / UiO-66 mixed matrix membrane for Sb(V) ions in tailings wastewater can only reach 41.5%, while the interception rate of PVDF / UiO-66-EDTA mixed matrix membrane can reach 93.4%, and while the interception rate of PVDF / UiO-66-EDTA mixed matrix membrane is improved, the water flux is not much lower than that of PVDF / UiO-66 mixed matrix membrane. From the results, PVDF / UiO-66-EDTA mixed matrix membrane has more advantages in treating tailings wastewater containing Sb(V) ions.
[0069] Table 2 PVDF / UiO-66-EDTA mixed matrix membrane
[0070]
[0071] PVDF / UiO-66 mixed matrix membrane only has interception effect on Sb(V) ions in tailings wastewater, that is, it has adsorption effect, and has almost no adsorption capacity for other metal ions (this is common sense). Combining the data in Table 1 and Table 2, it can be seen that the PVDF / UiO-66-EDTA mixed matrix membrane has interception effect on the three metal ions Sb(V), Cr(VI) and Pb(II), overcoming the disadvantages of PVDF / UiO-66 mixed matrix membrane with single adsorption object and poor adsorption effect, and when the interception rate is above 90%, the water flux can also be maintained at 850Lm -2 h -1 bar -1 The above is undoubtedly an important breakthrough for membrane treatment of tailings wastewater.
[0072] In summary, UiO-66-EDTA mixed matrix membrane has more advantages in treating tailings wastewater.
[0073] Since Sb(V) ions are the main research object and are easy to compare and simplify, Figure 2 The removal performance of the MOF-based mixed matrix membrane for treating tailings wastewater is based on the Sb(V) ion retention rate (right vertical axis) as the reference standard. Figure 2 The middle bar graph corresponds to the pure water flux (left ordinate), and ■ and ★ correspond to the removal rate of Sb(V) ions (right ordinate).
Claims
1. A method for preparing a MOF-based mixed matrix membrane for treating tailings wastewater, characterized in that The preparation method of MOF-based mixed matrix membrane for treating tailings wastewater is carried out in the following steps:
1. adding the UiO-66-EDTA composite material into a solvent for dissolution, and performing ultrasonic treatment to obtain a suspension; 2. Fully dissolving the suspension prepared in step 1 and polyvinylidene fluoride powder to form a casting solution, and then performing ultrasonic defoaming for 90 minutes; 3. Scrape the casting liquid obtained in step 2 onto a glass plate to form a liquid film; Fourth, place the glass plate with the liquid film in the air for pre-evaporation for 30s to 35s, then immerse it in deionized water at 27℃ to 29℃, and let it stand until the film and the glass plate are completely separated. Use tweezers to transfer the liquid film to another deionized water at room temperature and soak it for 24h to 25h to obtain a MOF-based mixed matrix membrane; The mass of the MOF-based mixed matrix membrane is composed of the UiO-66-EDTA composite material of step one, the solvent and the polyvinylidene fluoride powder of step two, wherein the added amount of the UiO-66-EDTA composite material is 1wt% to 6wt%, and the added amount of the polyvinylidene fluoride powder is 6wt% to 11wt%.
2. The method for preparing a MOF-based mixed matrix membrane for treating tailings wastewater according to claim 1, characterized in that The solvent described in step 1 is N,N-dimethylacetamide.
3. The method for preparing a MOF-based mixed matrix membrane for treating tailings wastewater according to claim 1, characterized in that The preparation method of the UiO-66-EDTA composite material described in step 1 is: (1) 240 mg of zirconium chloride was dissolved in 50 mL of acetone, and then 161 mg of terephthalic acid was added and ultrasonically mixed for 15 min to obtain a uniform precursor solution; (2) transferring the precursor solution into a polytetrafluoroethylene-lined autoclave and placing it in a 120° C. oven for constant temperature crystallization for 48 h, taking out the autoclave and naturally cooling it to room temperature; (3) After the obtained product was repeatedly washed with N,N-dimethylformamide and anhydrous ethanol, it was placed in a forced air drying oven and dried at 60°C for 12 h to obtain UiO-66 powder; (4) 1.582 g of EDTA-2Na was dissolved in 50 mL of water and stirred to form a clear and transparent solution, followed by adding 0.1 g of UiO-66 powder and stirring at 60 °C for 24 h; the mixture was filtered and washed with deionized water, the solid portion was retained, and finally dried at 100 °C to obtain a UiO-66-EDTA composite material.
4. The method for preparing a MOF-based mixed matrix membrane for treating tailings wastewater according to claim 1, characterized in that In step 2, the polyvinylidene fluoride powder is fully dissolved in the suspension by magnetic stirring for 24 hours.
5. The method for preparing a MOF-based mixed matrix membrane for treating tailings wastewater according to claim 4, characterized in that The rotation speed of the magnetic stirring in step 2 is 300 rpm.
6. The method for preparing a MOF-based mixed matrix membrane for treating tailings wastewater according to claim 1, characterized in that The specific process of step three is: using the glass plate as the substrate, setting the gap between the scraper and the glass plate to 200 μm, pouring the casting liquid on one side of the scraper, and quickly scraping a uniform liquid film on the glass plate by manual operation. The experimental conditions are room temperature and humidity of 40% to 50%.
Citation Information
Patent Citations
EDTA (Ethylene Diamine Tetraacetic Acid) modified UIO-66 (Zr) metal organic framework material as well as preparation method and application thereof
CN115490879A
Preparation method of polyvinylidene fluoride based metal organic framework hybrid membrane and hybrid membrane
CN116803475A